2019
DOI: 10.3390/ijerph16091571
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors and Fracture Risk: A Review of Current Evidence and Mechanisms Involved

Abstract: The number of patients with gastroesophageal problems taking proton pump inhibitors (PPIs) is increasing. Several studies suggested a possible association between PPIs and fracture risk, especially hip fractures, but the relationship remains contentious. This review aimed to investigate the longitudinal studies published in the last five years on the relationship between PPIs and fracture risk. The mechanism underlying this relationship was also explored. Overall, PPIs were positively associated with elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 106 publications
0
84
1
14
Order By: Relevance
“…However, we did not observe a dose-response relationship between risk of HFx and dose of PPI used. This is in contrast to other studies [11][12][13][14][15] , which demonstrated an association between dosage of www.nature.com/scientificreports/ PPI and HFx was dose-dependent. This difference might be explained by the use of different statistical analysis methods or the susceptibility of T2DM patients to HFx 5 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we did not observe a dose-response relationship between risk of HFx and dose of PPI used. This is in contrast to other studies [11][12][13][14][15] , which demonstrated an association between dosage of www.nature.com/scientificreports/ PPI and HFx was dose-dependent. This difference might be explained by the use of different statistical analysis methods or the susceptibility of T2DM patients to HFx 5 .…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with T2DM have an increased risk of fracture due to falls related to nervous and vascular disease 25,27 as well as changes in the microarchitecture that decrease bone strength and quality 28,29 . The effects of bone structure due to use of PPIs may be linked to malabsorption of calcium, hypergastrinemia, hypochlorhydria, hyperparathyroidism, and regulation of bone cells 15,30 . Previous studies have suggested that use of PPIs leads to increased gastric pH, and prolonged hypochlorhydria may reduce calcium ionization and affect intestinal absorption 15,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical significance lies in the association with lower calcium levels, which potentially points to an increased risk of developing osteoporosis. Long-term PPI use has indeed been associated with decreased bone mineral density and increased risk of fractures [36]. Because many patients use PPIs without evidence based indication [37][38][39], we believe that reevaluation of treatment indication in KTR on chronic PPI therapy might be of benefit.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the effect of PPIs on the BMD is usually reversible (Corley et al, 2010). Current studies claimed that hypochlorite due to PPI is the cause of bone fractures as hypohydrochloria and high gastrin levels reduced the mineral absorption and thereby producing a defect in the bone remodelling (Thong et al, 2019). Some authors claimed that PPIs directly altered bone regeneration and osseointegration (Mester et al, 2019).…”
Section: 879mentioning
confidence: 99%